Estimation of short‑duration rainfall intensity from daily rainfall values in Klang Valley, Malaysia - Al Mamun, Abdullah; Salleh, Md. Noor; Mohamad Noor, Hanapi (Springer International Publishing, 2018)
Data on intensity–duration–frequency or design rainfall are one of the most important information required for various hydrological and water resources studies. However, such crucial data are often unavailable in various parts of the world due to lack of enough rain gauging stations. It is not only tedious to determine design rainfall from the raw data but also occasionally impossible to calculate due to lack or absence of short-duration rainfall data. Generally, the manual rain gauges outnumber the automatic gauges, making it difcult to have adequate data on short-duration rainfall values, which is very important for urban hydrology. However, no graphical or mathematical relation could be found in the literature, which can be used for quick estimation of short-duration design rainfall from the daily rainfall data recorded by the manual stations. Annual maximum rainfall data from 143 rain gauging stations located at Klang Valley in Malaysia were used in this study. Statistical analyses and logarithmic graph ftting techniques were used to develop excellent correlation between short-duration rainfall and daily rainfall values for 96 automatic and 46 manual stations. Rainfall data analyze the design rainfall data of various duration and return periods. The 15, 30 and 45 min of short-duration rainfall, which is the most common rainfall duration in the study area, was observed to be 32.4%, 47.1% and 57.4% of the daily rainfall amount, respectively. The amount of rainfall during 1-, 2- and 3-h storm events contribute 64.9%, 76.5% and 80.9% of the daily rainfall. Such relations can be used for quick estimation of short-duration rainfall resulting in saving time, money and other resources